Blood flow to exercising limbs varies with age, gender, and training status - Koch, D. W.; Newcomer, S. C.; Proctor, D. N. (Canadian Journal of Applied Physiology, 2005)
Understanding the effects of physiological aging on blood flow to active skeletal muscle and its regulation during exercise has important functional, hemodynamic, and metabolic implications for our rapidly expanding elderly population. During peak exercise involving a large muscle mass, blood flow to the legs is lower in healthy older compared to younger persons; this results from central (reduced cardiac output) and peripheral (reduced leg vascular conductance) limitations. There is considerable variability in the literature concerning age-related changes in leg blood flow during submaximal exercise, with reports of similar or reduced leg blood flow and vascular conductance in older vs. younger subjects depending on the exercise intensity and the gender and training status of the subjects. However, all the studies involving non-endurance-trained subjects are consistent in that older subjects achieve the requisite leg blood flow at higher arterial perfusion pressures than young subjects, suggesting altered local vasoregulatory mechanisms with aging. Although the nature of these age- related alterations is poorly understood, we have preliminary evidence for augmented sympathetic vasoconstrictor responsiveness in the legs of older men during exercise, and blunted leg vasodilator responsiveness in older women. Systematic research will be needed in order to define the central and local mechanisms underlying these age- and gender-specific differences in muscle vascular responsiveness. Such information will be important for designing future interventions aimed at improving muscle blood supply and functional capacity in older persons.